The Prospect Science of Meniscus Preservation - Asep Santoso; Krisna Yuarno Pratama; Sholahuddin Rhatomy; Nicolaas C. Budhiparama (Indonesian Hip and Knee Society (IHKS), 2022)
The meniscus plays a role in stabilizing (secondary) knee joints by load transmission and reducing the contact stresses on knee joint cartilage. Meniscal tear more commonly involves the young patient and may be associated with ligament injuries. Meniscal injury also can be associated with some congenital anomaly. The meniscus injury treatment is challenging and most commonly treated with excision.Excision of the meniscus is associated with poor clinical outcomes, and high chance of early cartilage degeneration. Current meniscus repair techniques are still associated with common re-admission for surgery and poor clinical outcomes. To improve the patient- reported outcomes, the current basic research project should focus on enhancing meniscus healing and replacing meniscus tears.